A point to the South - Cattani, Maria Lucia (PORTO ARTE: Revista de Artes Visuais, 2016)
This artist’s book is an integral part of a work entitled "Um ponto ao sul" (A point to the South), which consists of a unique bookwork placed in the rare books collection of the Biblioteca Pública do Estado do Rio Grande do Sul, Brazil, and an offset print version of the same book in an edition of 1080. The unique book was developed from an invented script which was laser cut onto 12 wood blocks. The page illuminations are based on fragments of the wall decorations in the Biblioteca.